Select constitutions - Kapur, Anup Chand (New Delhi, 2016)
Select Constitutions is a book that is designed to provide you with an in-depth analysis of a number of governments around the world. The governments included here are those of Switzerland, England, India, US and the USSR. This book has been written with the intent of helping those students who are appearing for university exams, as well as for those students who are appearing for a wide range of competitive examinations. The book has been divided into two distinct parts. The first one is titled The Government of The United Kingdom, while the second part is The Government of The Indian Republic ? The Nationalist Movement. Each part of the book is inclusive of various sub-topics. The first part of this book includes five sub-parts, namely The Government of United States, The Government of France - The Government of Canada, The Government of Switzerland, The Government of Japan and The Government of The People's Republics of China. The second part includes topics named The Indian National Congress and the Demand for Parliamentary Institutions, The Rise of Muslim Communalism, The British Legacies, Making of the Constitution: Basic Decision and objectives Fundamental Rights, Directive Principles of State Policy and Fundamental Duties, The President, The Council of Ministers Parliament, The Supreme Court, The Union and the States, The State Executive, The State Legislature, The State Judiciary, Services under the Union and the States, Administrative Tribunals, Elections and Parties - The Indian Political System and finally the Index. The 16th edition, 2006 edition of Select Constitutions has been published by S Chand & Co Ltd, in the year 2010 and is available in paperback. Key Features The book is ideal for anyone preparing for competitive examinations. It gives you insight into the workings of various governments.
Keywords: Constitutions